Penghitungan kumpulan gambar rajah daripada hasil darab langsung dua semikumpulan bebas - Abd Ghafur Ahmad, (Penerbit ukm, 2005)
This paper computes the generators of diagram group from the direct product of two free semigroups that is the presentation S=[X,Y|xy=yx(x∈X,y∈Y)] . The form of the graph of all pictures contain in this direct product is considered. The graph obtained is connected according to the length of word and the exponent sum of x and y. Then the number of the generator of the graph group can be determined